ملامح الرؤية الكونية التوحيدية عند محمد المبارك - سرياني مروه (University of eloued جامعة الوادي, 2025)
تهدف هذه الدراسة الموسومة بـ: ملامح الرؤية الكونية التوحيدية عند محمد المبارك إلى إبراز الرؤية الكونية التوحيدية في فكره، وذلك من خلال استقراء نظرته إلى الوجود، وموقفه من القيم والأخلاق، ونقده للتصورات الغربية ذات الطابع المادي. وقد عرضت ذلك من خلال محاور أساسية أبرزها: التوحيد كأساس للرؤية الكونية، مكانة الإنسان في الكون، المنظومة الأخلاقية، ورؤيته للتاريخ والاجتماع الإسلامي. وتُظهر نتائج هذه الدراسة أن فكر محمد المبارك يقدّم رؤية كونية شاملة ومتكاملة تنطلق من التوحيد كأساس لفهم الكون والإنسان والحياة، وتسعى إلى بناء مجتمع يؤمن بالقيم، ويوازن بين الثوابت الشرعية ومتطلبات الواقع المعاصر. "This study، tagged ""Features of the Monotheistic Worldview"" according to Dr. Mohammad Al-Mubarak، aims to highlight the monotheistic worldview in his thought، and that by examining his view on existence، his position on values and morals، and his criticism of materialistic Western concepts. I presented these ideas through the main axes، most notably: - monotheism as the foundation of the worldview. - the status of the human being in the universe - the ethical system - and Mohammad Al-Mubarak's view of Islamic history and society. The results of this study reveal that Mohammed Al-Mubarak's thought offers a comprehensive and integrated global vision that starts from monotheism as a basis for understanding the universe، humanity، and life، and also seeks to build a society that believes in values، and makes balance between religious principles and the requirements of contemporary reality
Keywords: محمد المبارك; الرؤية الكونية; لتوحيدية; Mohammad Al-Mubarak; Monotheistic Worldview